Lived experiences of students with virological failure on antiretrovirals at a university in Limpopo - Mahlodi P. Maphakela; Mokoko P. Kekana; Eric Maimela (AOSIS, 2023)
Background: Human immunodeficiency virus (HIV)-positive students at a rural university in Limpopo province are followed-up according to the national guidelines for the treatment of HIV. Blood monitoring revealed that some students on antiretroviral (ARV) treatment were not virologically suppressed despite adherence and compliance being emphasised at every visit. Objectives: The study sought to identify the students' experiences that were hindering the viral load from improving. Method: A two-phase qualitative, explorative, descriptive study design was followed. Convenience purposive sampling methods were taken on. By means of a semi-structured interview guide, face-to-face interviews were directed. Thematic content analysis was applied. Results: Non-disclosure, noisy ARV packaging, stigma, and service delivery played a role in determining levels of student adherence and compliance with ARVs in the study sample. Conclusion: Study findings suggest practical recommendations to improve compliance among students on ARVs: provision of HIV education to all students to help reduce stigma and make it easier to disclose HIV status; use of user-friendly noise-free packaging by pharmaceutical companies to enclose medication, such as blister packs; a supermarket approach in service delivery points to reduce the stigmatising effects of consulting rooms for ARV services. Contribution: There is scope to examine the relevance of these findings for other students in the country, to compare them, and to use material from larger studies to guide targeted interventions that could improve adherence among young people.